Design of Python Programming Learning Media Interaction Design Using the UCD Method - Ade Arya Ilham (Publikasi Indonesia, 2024)
Programming learning media plays an important role in helping learners master programming languages such as Python. This research aims to design an effective interaction design on Python-based programming learning media using the User Centered Design (UCD) Method, which is a design approach that puts the user at the center of attention, ensuring that the resulting product is in accordance with the user's needs and preferences. User needs analysis, prototyping, and iterative eval_uation are all part of UCD's research methodology. The analysis of user needs will identify user profiles, learning problems, and interface preferences. The design process will involve creating a prototype of learning media that takes into account the needs and characteristics of the user. Iterative eval_uations will be used to gather user feedback and help improve the design.